Non-Invasive Colorectal Cancer Screening: An Overview - Tepus, Melanie (Gastrointest Tumors, 2020)
BACKGROUND: Colorectal cancer (CRC) follows a protracted stepwise progression, from benign adenomas to malignant adenocarcinomas. If detected early, 90% of deaths are preventable. However, CRC is asymptomatic in its early-stage and arises sporadically within the population. Therefore, CRC screening is a public health priority. SUMMARY: Faecal immunochemical test (FIT) is gradually replacing guaiac faecal occult blood test and is now the most commonly used screening tool for CRC screening program globally. However, FIT is still limited by the haemoglobin degradation and the intermittent bleeding patterns, so that one in four CRC cases are still diagnosed in a late stage, leading to poor prognosis. A multi-target stool DNA test (Cologuard, a combination of NDRG4 and BMP3 DNA methylation, KRAS mutations, and haemoglobin) and a plasma SEPT9 DNA methylation test (Epi proColon) are non-invasive tools also approved by the US FDA, but those screening approaches are not cost-effective, and the detection accuracies remain unsatisfactory. In addition to the approved tests, faecal-/blood-based microRNA and CRC-related gut microbiome screening markers are under development, with work ongoing to find the best combination of molecular biomarkers which maximise the screening sensitivity and specificity. KEY MESSAGE: Maximising the detection accuracy with a cost-effective approach for non-invasive CRC screening is urgently needed to further reduce the incidence of CRC and associated mortality rates.